The Implementation of Child-Friendly Education in the Learning Environment of Elementary-Age Santri in Islamic Boarding Schools - Fadhil Nur Hidayat; Aziz Mukhamad Thoha (Universitas Garut, 2026)
This study analyzes the implementation of child-friendly education for elementary school-aged santri at Hidayatul Qur'an Islamic Boarding School, addressing a gap in literature on daily practices within such settings. Using a qualitative case study, data were gathered via observation and interviews with administrators, educators, and students. Analysis followed Miles, Huberman, and Saldaña's interactive model. Findings indicate implementation through three primary strategies: (1) ensuring a safe, developmentally-appropriate learning environment; (2) building dialogical educator-student relationships; and (3) applying discipline focused on habit formation and constructive communication. This integrated approach fosters a positive learning climate and enhances student engagement. The study concludes that child-friendly education is viably cultivated through everyday pedagogical practices in Islamic boarding schools, demonstrating their potential as holistic learning environments for child development.